2022
DOI: 10.1002/ajh.26627
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen‐haploidentical transplantation for relapsed/refractory acute myeloid leukemia: Better leukemia‐free survival with bone marrow than with peripheral blood stem cells in patients ≥55 years of age

Abstract: The best stem cell source for T-cell replete human leukocyte antigen (HLA)-haploidentical transplantation with post-transplant cyclophosphamide (PTCy) remains to be determined. In this European Society for Blood and Marrow Transplantation retrospective study, we analyzed the impact of stem cell source on leukemiafree survival (LFS) in adult patients with primary refractory or relapsed acute myeloid leukemia (AML) given grafts from HLA-haploidentical donors with PTCy as graft-versus-host disease (GVHD) prophyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Indeed, Bashey et al observed lower relapse incidence with peripheral blood stem cells than with bone marrow after Haplo transplantation with post-transplant cyclophosphamide in a large registry study [36]. However, we could not confirm these findings in a large cohort of patients with active AML at transplantation [39]. Post-transplant maintenance therapies with FLT3 tyrosine-kinase inhibitors in case of FLT3-ITD AML [42], hypomethylating agents [43,44] or pre-emptive DLI [45][46][47] should be investigated in this group of patients.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Indeed, Bashey et al observed lower relapse incidence with peripheral blood stem cells than with bone marrow after Haplo transplantation with post-transplant cyclophosphamide in a large registry study [36]. However, we could not confirm these findings in a large cohort of patients with active AML at transplantation [39]. Post-transplant maintenance therapies with FLT3 tyrosine-kinase inhibitors in case of FLT3-ITD AML [42], hypomethylating agents [43,44] or pre-emptive DLI [45][46][47] should be investigated in this group of patients.…”
Section: Discussioncontrasting
confidence: 62%
“…Also, there was a higher proportion of patients given bone marrow stem cells in the Haplo group. Indeed, bone marrow has been associated with a lower incidence of GVHD than peripheral blood stem cells in the Haplo setting [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 , 5 While the association of a calcineurin inhibitor and an antimetabolite with or without anti-thymocyte globulins (ATG) has remained the standard GVHD prophylaxis in the last decades, 6 , 7 post-transplant administration of cyclophosphamide (PTCy) has proven to be an efficient way to prevent GVHD, not only in the HLA-haploidentical allo-HCT setting but also in HLA-matched or 1/10 HLA-mismatched allo-HCT. 8 , 9 , 10 , 11 , 12 However, the precise mechanisms of GVHD prevention by PTCy (and particularly the potential role of regulatory T cells (Treg)) remains debated.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transplant cyclophosphamide (PTCy)-based GVHD prophylaxis has revolutionized the field of human leukocyte antigen (HLA)-haploidentical hematopoietic cell transplantation (Haplo-HCT) [ 5 , 6 ]. Consequently, Haplo-HCT is nowadays frequently used as treatment for relapsed/refractory AML patients [ 7 ]. A recent systems biology analysis in patients with PTCy-based GVHD prophylaxis demonstrated different signatures associated with GVHD and GvL effects [ 8 ].…”
mentioning
confidence: 99%